ANALISIS LOCATION QUOTIENT HASIL-HASIL PERTANIAN DI PROVINSI ACEH - Via Sofiana; Cut Putri Mellita Sari (Jurnal Ekonomi Pertanian Unimal, 2022)
This study determined the leading commodities in the rice agricultural sector in each regency/city in Aceh province. This study used the quantitative method. The object was the data on the development of the production level of rice agricultural sectors at the Central Bureau of Statistics of Aceh Province. The data analyzed was secondary data, namely data on the production of the rice agricultural sector in Aceh Province in 2018-2021. The results indicated that from the Location Quotient (LQ) analysis, rice production was the leading sub-sector in Aceh Province from 2018 to 2020. The results of the Dynamic Location Quotient (DLQ) analysis revealed that rice production in Aceh Province has changed from the base sector to a non-basic sector such as Aceh Singkil Regency. Meanwhile, Central Aceh was the contrary, from the non-base sector to the basis as happened in Southeast Aceh Regency.